HUBUNGAN SELF CONTROL TERHADAP PERILAKU BULLYING PADA REMAJA DI SMP NEGERI 2 BANYUPUTIH - Raup Padillah; Febrian Rhomadoni; Harwanti Noviandari, (BIMBINGAN DAN KONSELING BANYUWANGI, 2022)
This study aims to examine the relationship between self control and bullying behavior at SMP Negeri 2 Banyuputih. The method used in this research is descriptive quantitative method. The subjects in this study were 79 students who were selected by purposive sampling technique. The results of this study indicate a relationship between Self Control and Bullying Behavior. From the results of the hypothesis test, it can be seen that the calculated F value is 467,256 with a significance level of 0.00 < 0.05, it means that the regression model based on the research is significant. This proves that Ha is accepted and H0 is rejected, because there is a relationship between the variable X (Self Control) and bullying behavior.